KARAKTERISTIK PEMBELAJARAN BIPA PROGRAM CULTURA DI UNIVERSITAS ISLAM SULTAN AGUNG - Chamalah, Evi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Teaching Indonesian does not only teach about language but indirectly teaches Indonesian culture. However, each BIPA learning place has different characteristics. This difference certainly has a positive impact. This research aims to examine the characteristics of BIPA Cultura learning at Unissula. This research is a type of qualitative descriptive research by describes the research results using text directly. The data collection technique in this research was carried out by documenting and interviewing BIPA teachers, BIPA friends, and the results of BIPA learning activities. The data obtained is presented in a detailed descriptive qualitative manner. Unissula's BIPA Cultura program has characteristics that differentiate it from other BIPA programs, namely the integration of Islamic insight, Indonesian insight and linguistics in the learning process. This program focuses on teaching Indonesian and introduces various aspects of Islamic culture and values ​​in Islamic academic culture.